Exploring ideal scent detection dog characteristics for successful professional deployment as derived from face-to-face structured interviews with professional scent detection dog handlers - Pascalle E. M. Roulaux; Claudia M. Vinke; Ineke R. van Herwijnen; Saskia S. Arndt (PLoS ONE, 2026)
Scent detection dogs (SDDs) require certain behavioral characteristics for successful professional deployment. We aimed to provide insight into these characteristics by tapping into professional SDD handlers’ knowledge and experience. We conducted a first round of informal interviews with Dutch professional SDD handlers, which led to the derivation of a list of 24 characteristics. We subsequently used this list in structured interviews and had participants (N = 110) indicate how their ‘ideal SDD’ would score on a scale from 0 to 100 (ideal scores) and how reluctant they would be to see an actual dog deviate from their ideal image for each characteristic (allowed deviation scores). We compared the allowed deviation scores to the variation in the ideal scores. Additionally, we compared ideal dog characteristics for professional deployment versus recreational deployment by civilians to assess how these characteristics are relevant to professional deployment of SDDs. Professional participants were the most reluctant to make concessions for these SDD characteristics: neurotic, insecure, imperturbable (environment), scent-oriented, independent, confident, persistent, and resilient . Seven of these eight characteristics were also among those with the least variation in ideal scores between professionals. Four ‘ideal SDD’ characteristics differed significantly between civilians and professionals: civilians desired lower scores for unreserved , impulsive , excited and possessive . Three allowed deviation scores differed significantly: professionals were more reluctant to make concessions for unreserved , while civilians were more reluctant to make concessions for precise and possessive . Focusing future on the characteristics that professional handlers are reluctant to see deviate from their ideal image could enhance SDD selection and training for professional deployment and provide a basis for the development of behavioral tests or specific observations for professional SDD selection in the future. We pinpoint the characteristics of neurotic , insecure , imperturbable (environment), scent-oriented , independent , confident , persistent and resilient as possible focus points in such research.